Persepsi Perhatian Orang Tua Terhadap Motivasi Belajar Matematika Siswa Kelas XI di SMA Plus Ibadurrahman - Ahmad Fahrudin (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine the perception of parental attention to the learning motivation of Class XI students at SMA Plus Ibadurrahman. The research conducted is qualitative research using a quantitative approach used to examine data and statistical analysis. The research method used is the survey method, the data collection techniques used in this study are interviews, documentation, and questionnaires, and the measurement scale used is the Likert scale. The population in this study were all students of Class XI SMA Plus Ibadurrahman, totaling 96 students. The sample in this study was 78 students of class XI obtained by using the Slovin formula. After the researcher analyzed the data, the calculation results were obtained, namely tcount = 7.0889 and ttable = 1.99167 with a significance level of 5% so that it can be concluded that tcount 7.0889 ttable 1.99167 then Ho is rejected and Ha is accepted which means that there is an influence between the X variable and the Y variable, which states that there is an influence of the perception of parental attention on the learning motivation of class XI students at SMA Plus Ibadurrahman